Gas6/Axl Axis Activation Dampens the Inflammatory Response in Osteoarthritic Fibroblast-like Synoviocytes and Synovial Explants - Juliana P. Vago; Natália Valdrighi; Esmeralda N. Blaney-Davidson; Daniel L. A. H. Hornikx; Margot Neefjes; María E. Barba-Sarasua; Nathalie G. M. Thielen; Martijn H. J. van den Bosch; Peter M. van der Kraan; Marije I. Koenders; Flávio A. Amaral; Fons A. J. van de Loo (MDPI AG, 2023)
Osteoarthritis (OA) is the most prevalent joint disease, and it is characterized by cartilage degeneration, synovitis, and bone sclerosis, resulting in swelling, stiffness, and joint pain. TAM receptors (Tyro3, Axl, and Mer) play an important role in regulating immune responses, clearing apoptotic cells, and promoting tissue repair. Here, we investigated the anti-inflammatory effects of a TAM receptor ligand, i.e., growth arrest-specific gene 6 (Gas6), in synovial fibroblasts from OA patients. TAM receptor expression was determined in synovial tissue. Soluble Axl (sAxl), a decoy receptor for the ligand Gas6, showed concentrations 4.6 times higher than Gas6 in synovial fluid of OA patients. In OA fibroblast-like synoviocytes (OAFLS) exposed to inflammatory stimuli, the levels of sAxl in the supernatants were increased, while the expression of Gas6 was downregulated. In OAFLS under TLR4 stimulation by LPS (Escherichia coli lipopolysaccharide), the addition of exogenous Gas6 by Gas6-conditioned medium (Gas6-CM) reduced pro-inflammatory markers including IL-6, TNF-α, IL-1β, CCL2, and CXCL8. Moreover, Gas6-CM downregulated IL-6, CCL2, and IL-1β in LPS-stimulated OA synovial explants. Pharmacological inhibition of TAM receptors by a pan inhibitor (RU301) or by a selective Axl inhibitor (RU428) similarly abrogated Gas6-CM anti-inflammatory effects. Mechanistically, Gas6 effects were dependent on Axl activation, determined by Axl, STAT1, and STAT3 phosphorylation, and by the downstream induction of the suppressors of the cytokine signaling family (SOCS1 and SOCS3). Taken together, our results showed that Gas6 treatment dampens inflammatory markers of OAFLS and synovial explants derived from OA patients associated with SOCS1/3 production.